The tumour/normal tissue ratio of Keap1 protein is a predictor for lymphovascular invasion in colorectal cancer: a correlation study between the Nrf2 and KRas pathways. (14th October 2022) - Chang, Liang-Che; Fan, Chung-Wei; Tseng, Wen-Ko; Chen, Jim-Ray; Hua, Chung-Ching
Abstract: Purpose: Oxidative stress has impacts on the KRas and Nrf2/Keap1 pathways, which have multiple interactions with each other and play important roles in colorectal cancer (CRC). This study investigated the expressions of proteins in the KRas and Nrf2/Keap1 pathways and their associations with clinicopathological features in CRC. Methods: The protein levels of Nrf2, Keap1, Bach1, p62, HO1, KRas, Erk, Raf1 and PI3K in both the tumour and normal tissues of 60 CRC subjects were determined by Western blot and their T/N (tumour/normal tissue) ratios were correlated with clinicopathological features. Results: The T/N ratios of proteins in the KRas and Nrf2/Keap1 pathways had correlation patterns and proximity profiles in cluster dendrograms different in CRC with different status of lymphovascular invasion (LVI) or lymph node/distant metastases. The Keap1 protein T/N ratio was a significant predictor (odd ratio: 2.24; 95% confidence interval: 1.26 − 4.38) of LVI, which in turn predicted metastases (11.0; 3.49 − 39.8). Conclusion: The interactions between the KRas and Nrf2/Keap1 pathways may be affected differently by LVI and metastases, and the protein T/N ratio of Keap1 may be helpful for predicting LVI in CRC.